(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The Dokan Formation (Cenomanian) has been studied within the Azmar anticline in Sulaymaniyah Governorate (about 4 km northeast of the city center). The field description shows that the Dokan Formation is composed mainly of light-gray limestone rocks and lead-gray marly limestone with thin beds of dark-gray shale. The thickness of the Formation in the studied section is 18 m; The lower and upper contacts of the Dokan Formation are conformable with the Balambo Formation and the Gulneri Formation, respectively. The petrographic study of (55) thin sections reveal the following components: planktonic and benthonic foraminifera, calcospheres, some echinoderm bioclasts, and lesser proportions of ostracods. Many diagenetic processes (dissolution, cementation, chemical and physical compaction, etc.) affected the rocks of the Formation. Two main microfacies are distinguished: the first one is lime mudstone microfacies, and the second is lime wackestone microfacies; these, in turn, are divided into six sub-microfacies. Comparing all microfacies with the standard microfacies indicates that the Dokan Formation was deposited in the zone that extended from the outer shelf to the upper slope environments.